2003
DOI: 10.1086/377263
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Encephalitis in a Child with Left‐Side Weakness

Abstract: West Nile virus typically causes self-limited fever with flulike symptoms; pediatric cases are rare. We report a unique case involving a 7-year-old girl with left-side weakness and focal temporal lobe findings resembling herpes encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…2,9,[11][12][13][14][15][16] In the early 1980s, WNV was isolated from the brains of 3 children who died of encephalitis within the same state in India. 23 During an unusual outbreak in Sudan in 2002, all 31 of the probable cases identified were among children Ͻ13 years of age, with most cases in those aged Յ5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,9,[11][12][13][14][15][16] In the early 1980s, WNV was isolated from the brains of 3 children who died of encephalitis within the same state in India. 23 During an unusual outbreak in Sudan in 2002, all 31 of the probable cases identified were among children Ͻ13 years of age, with most cases in those aged Յ5 years.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,16 However, encephalitis mimicking herpes simplex virus infection, poliomyelitis-like syndrome, myocarditis, hepatitis, chorioretinitis, and vitreitis have also been described as complications of WNV infections among children. 3,9,13,15,17 Routine clinical laboratory tests are not generally of use in distinguishing WNV infection from other viral infections. Among limited clinical data published on pediatric case subjects with WNND, cerebrospinal fluid findings include mild-tomoderate leukocytosis and mildly elevated protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging may show leptomeningeal thickening and contrast enhancement 43. The T2W and FLAIR sequences show patchy white matter hyperintensities 4446. These lesions typically do not enhance with contrast.…”
Section: Diagnosis Of Cns Viral Infectionsmentioning
confidence: 99%
“…Magnetic resonance imaging studies of patients with WNV-CNS have identified several patterns of involvement, including leptomeningeal enhancement intracranially [51,67], abnormalities in the basal ganglia and thalamus [33,36•,68,69], temporal lobe [70], and the substantia nigra [71] and pons [36•]. Among patients with WNV-CNS with acute flaccid paralysis, abnormal enhancement in the cauda equina [36,51] and anterior regions of the spinal cord [49,57] also has been described.…”
Section: Neuropathologic and Neurodiagnostic Findingsmentioning
confidence: 99%